PENGARUH METODE CERAMAH DAN STIMULASI TERHADAP PENGETAHUAN DAN SIKAP SISWA TENTANG KESEHATAN REPRODUKSI REMAJA DI SMK SWASTA TRISAKTI PEMATANGSIANTAR TAHUN 2017 - jane wilda irmawati sirait (Jurkessutra : Jurnal Kesehatan Surya Nusantara, 2022)
AbstractIn adolescence information about seual problems should begin to be given so that adolescents do not get misinformation rom sources that are not clear. Based on interviews conducted on 10 students 8 people do not understand about adolescent reproductive health and 2 people say understand about adolescent reproductive health but can not give an explanation. This study aims to determine the influence of lecture methods and simulation methods on students knoeledge and attitudes about adolescent reproductive health. The research was conducted at SMKSwasta Trisakti Pematangsiantar period from January to June 2017. The sample size is 62 people,with sampling technique with purposive sample. Data collection used primary data by distributing qustionnaries and analyzed by using t-test. The result o Lecture Method study hadan effect on the increase of kwnoledge and attitude of student before the treatment of knowledge 6.61 and attitude of 31,00 value t -2,763 p =  0,010, after the treatment of knowledge 8,39 and attitude 38,29 t = -862 p = 0,000 and method Stimulation effect on the increase of knowledge and attitude of student before knowledge treatment 6,77 and attitude 31,90 after knowledge treatment 10,16 and attitude 47,32 t = -11,261 p = 0,000. The stimulation method has more influence to increase the knowledge and attitude ofstudents about adolescent reproductive health t = -4,503 p = 0,000. For Trisakti Private Vocational School is expected to use stimulation method in the from of sociodrama to improve students knowledge and attitude about reproductive health especially about ree sex, drug use and HIV/AIDS patient and expected to be given separately in the institutions local concent.